2019
DOI: 10.1186/s40634-019-0175-7
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor levels in leukocyte-poor platelet-rich plasma and correlations with donor age, gender, and platelets in the Japanese population

Abstract: Background Clinical application of platelet-rich-plasma (PRP) has been accelerated to investigate early recovery from various musculoskeletal conditions. It involves the promotion of tissue damage repair through the action of multiple growth factors at physiological concentrations. The composition of PRP differs based on many factors, which may include age and gender. Therefore, we analyzed correlations between age, gender, and platelet counts in PRP with growth factors in Japanese subjects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 65 publications
(70 reference statements)
2
62
0
2
Order By: Relevance
“…Therefore, TGF-β1 can be used to treat a variety of disorders of the musculoskeletal system while PRP serves as a source for therapeutic purposes. No statistically significant difference was found between TGF-β1 level in PRP in the patients of different genders (p = 0.4), which is consistent with the literature data [25,30,31]. In women, the content of cytokine was 207.13 ± 16.28 ng/ml, and in men 196.36 ± 22.42 ng/ml (Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, TGF-β1 can be used to treat a variety of disorders of the musculoskeletal system while PRP serves as a source for therapeutic purposes. No statistically significant difference was found between TGF-β1 level in PRP in the patients of different genders (p = 0.4), which is consistent with the literature data [25,30,31]. In women, the content of cytokine was 207.13 ± 16.28 ng/ml, and in men 196.36 ± 22.42 ng/ml (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Data on the dependence of TGF-β1 content in PRP on the age are quite contradictory. Some studies showed that the content of TGF-β1 in PRP does not depend on the age of the studied patients [25,30]. Whereas, J. Evanson et al found that people up to 25 years old had higher cytokine levels in PRP than those of older age groups [31].…”
Section: Patientmentioning
confidence: 98%
“…On the other hand, we examined the ability of the combination products to retain or expel the supernatant rich in cytokines and growth factors, using PDGF assessments as representative of alpha granule cargo exocytosis [16]. To prepare the PRF, we pooled PRPs from twelve subjects; we chose this model to obtain meaningful reproducible results, getting rid of inter-donor variability [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Leukocyte platelet concentrates contain significant number of granulocytes and monocytes, which produce proinflammatory cytokines: tumor necrosis factor α (TNFα), interleukins 1β, 6 and 8. These cytokines induce the expression of genes that promote the destruction of the extracellular matrix and enhance inflammation, including genes of proinflammatory interleukins, prostaglandins, inducible NO-synthase, cyclooxygenase 2 and metalloproteinases [40,48,49]. Despite a number of possible negative effects, leukocyte platelet concentrates can promote healing and regulate inflammation, in particular enhance the synthesis of growth factors and have a pronounced antimicrobial effect, so they should not be completely excluded from clinical application [17].…”
mentioning
confidence: 99%
“…While studying the cellular components of platelet concentrates, insufficient attention is paid to the number of erythrocytes [16]. Some studies have shown that the number of red blood cells in PRP is minor because their count is reduced by 90 % compared with whole blood [9,40]. However, erythrocytes can be harmful to cells due to increased oxidative damage and affect the synthesis of extracellular matrix [23,24].…”
mentioning
confidence: 99%